The Role of Teacher Autonomy Support on Students’ Academic Engagement and Resilience - Ma, Qiangqiang (Frontiers in Psychology, 2021)
Learners have internal motivational resources that, when maintained, can enhance engagement, enthusiasm, resilience, and success. Learner engagement in educational tasks is a remarkable issue supporting the overall success of learners in higher education. Furthermore, building resilience in learners necessarily requires teachers’ efforts. Therefore, teacher support for autonomy is critical for augmenting appropriate outcomes, and it is deemed as a strong predictor of learners’ particular resources along with their motivational styles and educational achievement. As there is a dearth of studies that have considered teacher autonomy support and its noteworthy influence on learners’ resilience and engagement, the current review endeavors to concentrate on this motivational style in higher education. Successively, several implications are offered to illuminate the issue for teachers, students, teacher trainers, and educational administrators.